1993
DOI: 10.1016/0014-5793(93)81085-e
|View full text |Cite
|
Sign up to set email alerts
|

Functions of interleukin‐8 are mediated through thiol group(s) of IL‐8 receptor in human polymorphonuclear neutrophils

Abstract: Interleukin‐8, a neutrophi] chemotactic agent causes excessive accumulation of the cells in a number of inflammatory diseases. The activity has been shown to be mediated through a specific functional receptor present on the surface of neutrophils. No information is available about the amino acids constituting the IL‐8 binding domain of the receptor. Treatment of neutrophils with 5,5'‐dithio‐bis(2‐nitrobenzoic acid), a thiol‐specific modifier, at the concentrations of 0.4 mM and 1 mM reduced IL‐8 binding abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
1997
1997

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…IL-8 receptor is rapidly down-regulated with its ligand, the downregulated receptors are recycled back to the cell surface to accept fresh ligand, and this recycling process is intimately associated with the IL-8 induced migration of neutrophils [7,8]. We have shown that at least two cysteine residues are critical for binding of IL-8 to the receptor and also for receptor-mediated functions [9,10]. Recently, we have shown that a formyl peptide and serum-activated LPS up-regulated the functionally active IL-8 receptors in human polymorphonuclear neutrophils, which may have a potential role during inflammation [11].…”
Section: Introductionmentioning
confidence: 99%
“…IL-8 receptor is rapidly down-regulated with its ligand, the downregulated receptors are recycled back to the cell surface to accept fresh ligand, and this recycling process is intimately associated with the IL-8 induced migration of neutrophils [7,8]. We have shown that at least two cysteine residues are critical for binding of IL-8 to the receptor and also for receptor-mediated functions [9,10]. Recently, we have shown that a formyl peptide and serum-activated LPS up-regulated the functionally active IL-8 receptors in human polymorphonuclear neutrophils, which may have a potential role during inflammation [11].…”
Section: Introductionmentioning
confidence: 99%